PENGARUH PENERAPAN MODEL PEMBELAJARAN GROUP INVESTIGATION TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS X MIPA SMAN 1 BATUSANGKAR TAHUN PELAJARAN 2018/2019 - Sofni Fajriani (Departemen Matematika, 2019)
The ability of mathematical problem solving is one of the mathematics learning objectives to be achieved and evolved by learners itself. However, the students’ ability of mathematical problem solving are still not optimal and do not facilitated yet for improving those skills well. One of the efforts to improve the ability of mathematical problem solving is to apply Group Investigation (GI) learning model, aims to describe whether the learners’ ability of mathematical problem solving with GI model is better than learners’ ability of mathematical problem solving with direct learning. The type of research is quasi experiment with The Nonequivalent Posttest-Only Control Group Design.The authentication of the research hypotheses using t-test. Based on the analysis data concluded that the students’ability of mathematical problem solving who is applying group investigation model is better than the students’ ability of mathematical problem solving with direct learning. Keywords–Mathematical Problem Solving, Group Investigation, Direct Learning